The Effectiveness of the Combination of Quartet and Dart Games for Teaching Speaking - Jondriantoni (Journal of Innovative and Creativity, 2022)
This study investigates the use of the combination of Quartet and Dart games for teaching speaking. The main problem in teaching speaking of English as foreign language is how to stimulate and motivate students to speak. There are some media to teach speaking. This study proposes an alternative way for minimizing some problems that make the students hesitant to speak by using the combination of Quartet and Dart games. Quartet is a card game. There are totally 32 cards divided into 4 theme cards. Every card provides a brief description that will make the students read the description while waiting for the turn. The goal of the game is to collect a set of cards as many as possible. Dart game is an activity that is designed to challenge students to engage with the texts. The students are supposed to speak and to interpret the information carefully based on the Dart game. By using Quartet game, students will be able to speak well. It makes them speak based on the Quartet card. Quartet cards facilitate them with spoken vocabularies, grammar and structure of the text. Therefore, Dart game makes the students ready when they are going to express their ideas based on the instruction of Dart board. The objectives of this research are to find out whether the combination of Quartet and Dart games is effective to teach speaking to Junior High School‟s students and to find out whether the students are able to speak well by using the combination of Quartet and Dart games. The population was the eighth grade students of SMPS Yayasan Johan Sentosa Kabupaten Kampar in the academic year of 2014/2015. The number of population was 312 and sample was 36 students of VIII B for the try-out class and 37 students of VIII A as the experimental class. I used pre-experimental design in this research. When conducting the research, I used oral performance test to collect the data. The study showed that after the students were given treatment by using the combination of Quartet and Dart game, there was an increasing score from the pre- test and the post- test result about 72.86%. The tvalue was 27.69 and t-table was 1.69. Since the t-value is higher than the t-table, it can be concluded that the working hypothesis is accepted. It means that the combination of Quartet and Dart games is effective to improve students‟ speaking skills.